Effective interim leadership and management: development of a cyclical model of interim assignments. Issue 2 (10th July 2020) - Woods, Stephen A.; Diprose, Nick; Murphy-Diprose, Mary; Thomas, Geoff
Abstract : Purpose: This paper reviews literature on interim leadership and management through the lens of effective interim performance. The purpose of this review is to advance understanding of interim assignment performance and the antecedent individual psychological characteristics of effective interim leaders and managers, to improve the practice of managing interim leaders from a human resources (HR) perspective. Design/methodology/approach: The paper reports a targeted review of the literature on interim leadership and management. Findings: The main proposition from this review is that the influence of individual factors on interim performance operates within the stages and contexts of assignments. Accordingly, the authors propose a framework of the demands on interim assignments (the interim assignment cycle), comprising stages of preparation, entry, delivery and exit. The paper subsequently reviews evidence of the potential individual characteristics (focussing on individual differences in personality, leadership approach, motivation and competencies) of effective preparation and entry to an assignment, actions and performance during an assignment and exit/disengagement. Practical implications: The findings of the review have implications for the selection and placement of interims into organizations and their management once appointed. Originality/value: The main original contribution of the paper is to provide a framework around which interim assignments can be modelled and better understood. The paper discusses implications for future research, theory and human resource management practice and calls for a renewed research effort in this critical area of management and leadership.